Adaptation to the Future Climate: A Low Carbon Building Design Challenge - Barbhuiya, S.; Barbhuiya, Salim; Nikraz, Hamid (Elsevier BV, 2012)
In this paper an attempt has been made to assess the performance of an office building located in London (one of the case study buildings in CIBSE TM36: 2005) in relation to energy consumption, carbon emissions and potential for adaptability to the 2050s climate. Overheating is a particular issue in office buildings due to internal heat gains from computers and other electrical equipment. In addition, buildings in London are affected by the urban heat island, which is likely to intensify with warmer summer temperatures, reducing the capacity for night-time cooling of buildings. This paper proposes various passive design strategies which aim to address both mitigation (by reducing carbon emissions) and adaptation (by improving human comfort and reducing energy consumption).